2013
DOI: 10.1063/1.4820492
|View full text |Cite
|
Sign up to set email alerts
|

Communication: Synperiplanar to antiperiplanar conformation changes as underlying the mechanism of Debye process in supercooled ibuprofen

Abstract: In this Communication, we present experimental studies that put new insight into the puzzling nature of the Debye relaxation found in the supercooled liquid state of racemic ibuprofen. The appearance of D-relaxation in the loss spectra of non-hydrogen bonding methylated derivate of ibuprofen has proven that Debye relaxation is related solely with conformational changes of the carboxyl group, termed in this paper as synperiplanar-antiperiplanar. Our studies indicate that the presence of hydrogen bonding capabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 19 publications
1
18
0
Order By: Relevance
“…The molecular origin of the D-process observed in pure IBU has already been widely discussed. 47 51 Pure IBU has a big tendency to form H-bonded aggregates such as dimers and trimers (linear and cyclic), and the molecular origin of this process has been related to H-bonds dynamics. Correia and Affuard showed that the D-process in pure IBU is dominated by the cis - to trans -transformation of the carboxyl group (O=C—O—H) in IBU coupled to H-bonds dynamics.…”
Section: Resultsmentioning
confidence: 99%
“…The molecular origin of the D-process observed in pure IBU has already been widely discussed. 47 51 Pure IBU has a big tendency to form H-bonded aggregates such as dimers and trimers (linear and cyclic), and the molecular origin of this process has been related to H-bonds dynamics. Correia and Affuard showed that the D-process in pure IBU is dominated by the cis - to trans -transformation of the carboxyl group (O=C—O—H) in IBU coupled to H-bonds dynamics.…”
Section: Resultsmentioning
confidence: 99%
“…It is for example possible to change the volume without a concomitant change of the microscopic structure. Aging experiments can therefore give new information to the puzzle of what governs the relaxation time and could play a role analogous to that played by high pressure measurements [3,4,9], ultra stable glasses [10], and confinement [11,12], which have led to important experimental advances in glass science during the last couple of decades.…”
mentioning
confidence: 99%
“…The hydrogen-bonded structures can also give rise to an additional peak in the static structure factor at low Q-vectors [25,27], although the reverse is not true, a prepeak in the structure is not systematically associated with a slower than structural relaxation feature in the dynamics [28,29]. The family of liquids displaying a dielectric Debye process [30] includes, besides monoalcohols, secondary amides [31], protic ionic liquids [32], and several pharmaceuticals [33,34].…”
Section: Introductionmentioning
confidence: 99%